2011
DOI: 10.1016/j.ajpath.2010.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Determining Prostate Cancer-Specific Death through Quantification of Stromogenic Carcinoma Area in Prostatectomy Specimens

Abstract: We previously reported that reactive stroma grading in prostate cancer (PCa) is predictive of biochemical recurrence in prostatectomies and biopsies. In this study, we tested whether quantifying the percentage of reactive stromal grade 3 (RSG 3; stromogenic carcinoma pattern) in the entire tumor is predictive of PCa-specific death. Whole-mount prostatectomies operated by a single surgeon obtained between 1983 and 1998 were reviewed. Reactive stroma was evaluated as described previously, and areas of RSG 3 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 46 publications
3
50
0
Order By: Relevance
“…Both invasive and microinvasive mPCa is usually associated with reactive stroma changes, whereas human PCa typically elicits very little stromal reaction, at least when evaluated by histology alone[10]. It should be noted, however, that when reactive stroma is observed in human PCa patients by additional immunohistochemistry (IHC), it correlates with poor prognosis[31,32], and stroma derived from PCa patients (Carcinoma Associated Fibroblasts, CAF, [33]), can transform non-tumorigenic immortalized epithelial cell lines, clearly suggesting an important role for the stroma in human PCa. For a comparison of human and mouse PCa progression, see Figure 1.…”
Section: Human Versus Mousementioning
confidence: 99%
“…Both invasive and microinvasive mPCa is usually associated with reactive stroma changes, whereas human PCa typically elicits very little stromal reaction, at least when evaluated by histology alone[10]. It should be noted, however, that when reactive stroma is observed in human PCa patients by additional immunohistochemistry (IHC), it correlates with poor prognosis[31,32], and stroma derived from PCa patients (Carcinoma Associated Fibroblasts, CAF, [33]), can transform non-tumorigenic immortalized epithelial cell lines, clearly suggesting an important role for the stroma in human PCa. For a comparison of human and mouse PCa progression, see Figure 1.…”
Section: Human Versus Mousementioning
confidence: 99%
“…These protumorigenic actions of the tumor microenvironment are largely mediated via the secretion of paracrine‐acting factors, including chemokines, cytokines, growth factors, extracellular matrix (ECM) components and ECM remodeling enzymes 5. The importance of the tumor‐associated stroma as a driver of PCa progression and independent predictor of PCa prognosis is underscored by clinical data 6, 7. Thus, there is considerable interest in targeting the tumor microenvironment as a therapeutic strategy for PCa.…”
mentioning
confidence: 99%
“…Reactive stroma is found in most cancers and is typified by the coevolution of myofibroblasts (5)(6)(7). Importantly, the volume of reactive stroma relative to cancer is predictive of the rate of cancer progression in several tumor types (8)(9)(10)(11)(12)(13)(14)(15). Furthermore, in vivo modeling has shown that reactive stroma is tumor-promoting (16)(17)(18)(19).…”
mentioning
confidence: 99%